A frequency reconfigurable antenna for multiband mobile handset applications. Issue 9 (11th July 2017) - Zhang, Xiaoyan; Tian, Miao; Zhan, Aiyun; Liu, Zhiwei; Liu, Haiwen
Abstract: A frequency‐reconfigurable antenna is presented for multiband (GSM850/900/GLONASS1616/DCS1800/PCS 1900/UMTS/LTE2300/2500/WLAN) mobile handset applications. It mainly consists of radiating elements with two PIN diodes. By switching the ON/OFF states of the PIN diodes, the proposed structure can operate in three states: OFF–ON, ON–OFF, and ON–ON. When PIN diodes are in the OFF–ON states, the proposed antenna can cover the GSM850/900, PCS1900, and UMTS2100 bands by operating in Invented‐F antenna (IFA) mode. When PIN diodes are in the ON–OFF states, the antenna can cover the LTE2300/2500 and WLAN2400 bands in monopole mode. Moreover, when PIN diodes are switched to the ON–ON states, the designed antenna works in loop mode and its resonant frequencies include the GLONASS1616, DCS1800/1900, and LTE2500 bands. With the reconfigurable technique, the proposed antenna achieves a compact size of 15 × 28.5 mm 2 with high efficiency from 34% to 84.86% in the total frequency range.